A preliminary study on in-vitro lung cancer detection using e-nose technology - Thriumani , Reena; Zakaria, Ammar; Jeffree, Amanina Iymia; Hishamuddin, NA; Omar, Mohammad Iqbl; Adom, Abdul Hamid; M. Shakaff, Ali Yeon; Kamarudin, Latifah Munirah; Yusuf, Nurlisa; Hashim, Yumi Zuhanis Has-Yun; Mohamed Helmy, Khaled (2014)

(untitled)
The existing clinical diagnostics for lung cancer are mostly based on physics, biochemical and imaging techniques. The use of electronic nose (E-nose) system to detect volatile organic compounds (VOCs) in lung cancer cells or exhaled air breath of a patient is expected to be able to classify different volatile components leading to the diagnosis of lung cancer at an early stage. In this preliminary study, a commercialized E-nose consists of an array of 32 conducting polymer sensors (Cyranose 320) was used to detect and discriminate the VOCs emitted from cancer cells which is A549 (lung cancer cell line) between MCF7 (breast cancer cell line). Blank medium was used to obtain controlled value. The VOC profiles of each sample were characterized using a classification algorithm called k-Nearest Neighbors (KNN) to test and benchmark the performance of Enose in identifying VOCs of lung cancer from different cancer cell lines. The E-nose with KNN classifier was able to classify the VOCs of lung cancer cell with over 90% successful accuracy in 30 seconds. This study can conclude that e-nose is capable to rapidly discriminate volatile organic compounds of cancerous cells which generated during cell growth.